2017
DOI: 10.1534/genetics.116.195750
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Loss of the Dα1 Subunit in Drosophila melanogaster: Implications for Insecticide Resistance

Abstract: Nicotinic acetylcholine receptors (nAChRs) are a highly conserved gene family that form pentameric receptors involved in fast excitatory synaptic neurotransmission. The specific roles individual nAChR subunits perform in Drosophila melanogaster and other insects are relatively uncharacterized. Of the 10 D. melanogaster nAChR subunits, only three have described roles in behavioral pathways; Da3 and Da4 in sleep, and Da7 in the escape response. Other subunits have been associated with resistance to several class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 61 publications
(82 reference statements)
2
30
1
Order By: Relevance
“…This may be due to an absence of suitable variation in the DGRP. Studies with laboratory mutants suggest that resistance via these genes is associated with a loss of function that may involve a fitness cost 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to an absence of suitable variation in the DGRP. Studies with laboratory mutants suggest that resistance via these genes is associated with a loss of function that may involve a fitness cost 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Neonicotinoids target nicotinic acetylcholine receptors (nAChRs) that have vital roles in neurotransmission and behaviour in insects 4 , 5 . However, imidacloprid resistance via mutations in targets is not the most common resistance mechanisms, possibly due to associated fitness costs 6 . The overexpression of cytochrome P450 enzymes (P450s) more frequently underpins imidacloprid resistance 7 .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Creation and characterization of a Da1 gene knockout Ends out gene targeting was used to delete the entire 57 kb gene region of Da1, replacing it with a white + selectable marker cassette. 6 A line containing this deletion was then crossed to a Cre recombinase line to remove the white + cassette to establish the Da1 KO line. The first phenotypic test performed was for resistance to neonicotinoids.…”
Section: Receptors and Resistancementioning
confidence: 99%
“…Our study focussed on the phenotypic characterization of a loss of function mutation for the Da1 nAChR subunit gene. 6 Multiple phenotypes were identified. The Da1 receptor subunit had previously been implicated in insecticide resistance phenotypes, specifically to several members of the neonicotinoid class of insecticides but, in addition, the deletion of Da1 was shown to perturb sleep and courtship behavioral circuitry in ways that would be likely to impact fitness in a competitive field environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it did not significantly suppress the expression of Lsβ1 or Lsα8 , and the mortality rate of L. striatellus was high after dsLsβ1 or dsLsα8 ingestion (data not shown), but the importance of over‐expressed Lsβ1 and reduced expression of Lsα8 in cycloxaprid resistance could not be excluded. A previous study found that CRISPR‐Cas‐based gene editing could successfully knock down Drosophila nAChR expression, so this new technology needs to be explored further in L. striatellus to verify nAChR resistance function.…”
Section: Discussionmentioning
confidence: 99%